2005
DOI: 10.1021/jp0506033
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnO Nanoparticles in 2-Propanol by Reaction with Water

Abstract: We report on the synthesis of ZnO particles from Zn(CH(3)CO(2))(2) in 2-propanol as a function of the concentration of water, in the absence of a base such as NaOH. Particles with diameters of 3-5 nm are formed depending on time, temperature, and water concentration. The nucleation and growth are slower than in the presence of NaOH, and at longer times the increase in particle size is dominated by diffusion-limited coarsening. The rate constant for coarsening increases with increasing water concentration up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 32 publications
2
110
0
2
Order By: Relevance
“…From the inset graph in Fig. 4, we can clearly observe the increase of the wavelength of absorption peaks with enhancing water contents, which was associated with particle growth [46]. It is already reported that the dependence of particles size on the optical absorption spectra can be determined by using the effective mass model; details of the calculation can be found in Ref.…”
Section: Resultsmentioning
confidence: 75%
“…From the inset graph in Fig. 4, we can clearly observe the increase of the wavelength of absorption peaks with enhancing water contents, which was associated with particle growth [46]. It is already reported that the dependence of particles size on the optical absorption spectra can be determined by using the effective mass model; details of the calculation can be found in Ref.…”
Section: Resultsmentioning
confidence: 75%
“…Sol-gel method Sol-gel method, one of the widely used wet chemical methods in synthesizing various nanomaterials [15,[73][74][75], has been used for fabrication of ZnO QDs [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Among a number of reports on fabrication of ZnO QDs over the past decades, sol-gel method was the mostly used one due to its simplicity and cheapness.…”
Section: Chemical Methods On Synthesis Of Zno Qdsmentioning
confidence: 99%
“…By far, various kinds of synthetic approaches have been realized in fabricating such small ZnO QDs, which can be roughly divided into chemical methods and physical methods. Chemical methods involves sol-gel method [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], hydrothermal growth [41][42][43][44], thermal decomposition [45][46][47][48][49][50], electrochemical method [51][52][53][54], while physical methods involves PLA or PLD [55][56][57][58][59], MOCVD [60][61][62][63], sputtering [64][65][66], FSP method [67][68][69][70] and VPT deposition [71,72]. At present, all the methods can be divided into two parts as follow:…”
Section: Synthesis Of Zno Qdsmentioning
confidence: 99%
“…First, nanoparticles of transparent conductive oxides are synthesized, with suitable organic encapsulants as appropriate. For example, zinc oxide is easily synthesized in nanoparticle form (Figure 9.1) [10][11][12]. This may be achieved by precipitating zinc oxide out of, for example, zinc acetate in an isopropanol bath by addition of sodium hydroxide.…”
Section: Transparent Conductive Oxide Nanoparticlesmentioning
confidence: 99%